RIVIEW SISTEM PENGOLAHAN AIR PDAM TIRTA MANGUTAMA BADUNG - Muhamat, Oscar; Satya Kumara, I Nyoman; Budiastra, I Nyoman (Jurnal SPEKTRUM, 2024)
Water treatment in PDAM is a process in providing clean water supplies for the needs of the community of the district. The quality of the water produced must meet health and environmental standards to ensure that the water consumed is safe and decent for the user. This investigation aims to conduct a review of the water treatment system with a focus on the process of treatment of clean water ranging from raw water taken from the water tank to clean water that can be used by consumers. This process takes place at the intake where the raw water is sucked with two turbine pumps. Then the water is drained to the WTP (Water Treatment Plant) where the wTP is the main clean water treatment building. On the way to WTP there is a chemical process where water is mixed with poly aluminium chloride (PAC) fluid and chlorine to kill bacteria and purify the water. There are several parts of the room that process into clean water thats. the flokuator, then the sedimentation process, after the sedmentation process is continued to the filtration/filter process, in this process the filter uses silica sand as its filter so that the water is free from the dirt of the Sedimentation result, then after being clean water will enter the shelter or reservoir to continue to the customer's distribution system assisted by the booster pump.